Solidarity and salvation : the relationship between personal transformation and community in Dietrich Bonhoeffer - Shay, Donald J (Department of Religious Studies, 2023)
The major thesis of this dissertation is that personal transformation is grounded in community existence and experience. Bonhoeffer's understanding and experience of community provide key insights into this dynamic relationship. The development of his theology, shaped by his experience of struggle and solidarity in Nazi Germany, can also provide valuable resources for the struggle for justice and peace in South Africa, especially at this transitionary period in its history. The first chapter, A Theoretical Perspective: Sociality in Sanctorum Cornmunio and Creation and Fall, attempts to establish the theoretical underpinnings and centrality of Bonhoeffer's notion of 'sociality' which, it is argued, remains at the heart of his writings and praxis to the end of his life. It is in the concept of sociality that the influence of community on personal transformation is grounded. The second chapter, Reflections on Life in Community: Discipleship and Community in The Cost of Discipleship and Life Together, examines key issues at the heart of Bonhoeffer' s struggle for justice based in the concrete experience of intentional community life at the Finkenwalde seminary. In the context of the Church Struggle (Kirchenkampf) the community of faith was integral to helping pastors be obedient disciples in the midst of tremendous political struggles with an evil regime. The third chapter, A Vision - The Church for Others: Suffering, Metanoia and Responsibility in Ethics and Letters and Papers from Prison, explores the implications of personal transformation for a life of responsible discipleship. There is continuity in Bonhoeffer's thinking about personal transformation and community, but his context had changed during this period resulting in more emphasis on involvement in 'the world' and taking responsibility for changing the world.